Vision Therapy In The Modern Behavioural Optometry Practice: The History of Vision Therapy and Contemporary Approaches to Case Selection, Case Management, and the Delivery of Treatment. - Doyle, Michael P. (Optometry & Visual Performance, 2016)
Vision therapy can be found in the literature under the alternative descriptions of training or exercises; however, these terms imply a substantially motor-based regimen which has a tendency to narrow the scope or understanding to that offered in behavioural optometry. The following document reviews vision therapy as it applies today, with the objective being that of a guideline for optometrists new to, or considering, vision therapy.